2020
DOI: 10.1111/josh.12935
|View full text |Cite
|
Sign up to set email alerts
|

Bhutanese Refugee Youth: The Importance of Assessing and Addressing Psychosocial Needs in a School Setting

Abstract: BACKGROUND Traumatic exposure combined with significant stressors in resettlement place Bhutanese refugees at risk for mental health problems. Despite this, refugee youth often are reluctant to seek mental health services. Psychosocial support services, such as school‐based groups, offer one solution to this barrier to care. We had 2 aims in this study: (1) to describe the psychosocial needs of resettled Bhutanese refugee students; and (2) to evaluate the impact of skills‐based groups on these students' sense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Other research has found benefits for mental health and emotional well-being (Allen et al, 2018b;Arslan, 2018;Arslan et al, 2020;Li & Jiang, 2018;Šeboková et al, 2018;Zhang et al, 2018), academic success, hardiness, social inclusion, and life satisfaction (Abdollahi et al, 2020;Arslan et al, 2020;Brooms, 2016;Palikara et al, 2021;Scorgie & Forlin, 2019), self-esteem and associated positive outcomes (Foster et al, 2017;Peng et al, 2019), lowered school dropouts (Organisation for Economic Co-operation and Development [OECD], 2018;Uslu & Gizir, 2017), reduced likelihood of absenteeism, misconduct, school disengagement or students leaving school early without a qualification (Ibrahim & El Zaatari, 2019;Korpershoek et al, 2020;OECD, 2018), decreased feelings of alienation, isolation and disaffection or low social integration and social exclusion (Arslan et al, 2020;Palikara et al, 2021), and better performance and self-belief in abilities to succeed academically (Chun et al, 2016;Holloway-Friesen, 2019). Recent research shows that a sense of school belonging is a significant predictor of future employment, education, and training (NEET) (Parker et al, 2021), even up to 15 years post-school, and our understanding of the role that school belonging plays in the psychosocial adjustment of students who have experienced traumatic events or other forms of stress (Cardeli et al, 2020;Zhang et al, 2021) has immense implications for educational practice, as well as therapeutic benefits.…”
mentioning
confidence: 99%
“…Other research has found benefits for mental health and emotional well-being (Allen et al, 2018b;Arslan, 2018;Arslan et al, 2020;Li & Jiang, 2018;Šeboková et al, 2018;Zhang et al, 2018), academic success, hardiness, social inclusion, and life satisfaction (Abdollahi et al, 2020;Arslan et al, 2020;Brooms, 2016;Palikara et al, 2021;Scorgie & Forlin, 2019), self-esteem and associated positive outcomes (Foster et al, 2017;Peng et al, 2019), lowered school dropouts (Organisation for Economic Co-operation and Development [OECD], 2018;Uslu & Gizir, 2017), reduced likelihood of absenteeism, misconduct, school disengagement or students leaving school early without a qualification (Ibrahim & El Zaatari, 2019;Korpershoek et al, 2020;OECD, 2018), decreased feelings of alienation, isolation and disaffection or low social integration and social exclusion (Arslan et al, 2020;Palikara et al, 2021), and better performance and self-belief in abilities to succeed academically (Chun et al, 2016;Holloway-Friesen, 2019). Recent research shows that a sense of school belonging is a significant predictor of future employment, education, and training (NEET) (Parker et al, 2021), even up to 15 years post-school, and our understanding of the role that school belonging plays in the psychosocial adjustment of students who have experienced traumatic events or other forms of stress (Cardeli et al, 2020;Zhang et al, 2021) has immense implications for educational practice, as well as therapeutic benefits.…”
mentioning
confidence: 99%
“…A total of twelve (14.8%, 12/81) studies examined the association of peer relation factors and adolescent depressive symptoms [ 31 , 32 , 35 , 40 , 57 , 79 , 82 , 88 , 96 , 105 , 109 , 110 , 111 ]. Five (6.2%, 5/81) of these studies found that positive peer relations, support, or a sense of belonging was related to significantly reduced depressive symptoms and higher self-esteem [ 31 , 35 , 88 , 96 , 105 , 111 ]. In contrast, one study found that perceived support from peers of a different ethnicity was related to increased reporting of depressive symptoms [ 32 ], while another found no correlation between peer support and depressive symptoms [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies were included if they satisfied the following criteria: (a) included Asian adolescents who were 10 to 19 years of age; (b) identified a dimension of depression, such as depressive symptoms or depressed mood, as one of the outcome variables; (c) focused on the North American context; (d) examined the influence of psychosocial factors on depressive symptoms; and (e) were published in an English, peer-reviewed journal. Depressive symptoms can be assessed by different instruments, such as the Centre for Epidemiologic Studies Depression Scale [ 29 ], the 13-item Short Mood and Feelings Questionnaire [ 30 ], the Depression Self-Rating Scale for Children [ 31 ], the Beck Depression Inventory—Second Edition [ 32 ], and the Children’s Depressive Inventory [ 33 , 34 , 35 , 36 ]. Studies were excluded if they met the following conditions: (a) did not have an author; (b) did not have predicted depression status or depressive symptoms as an outcome; (c) did not include Asian American groups in the sample of a study; (d) addressed adolescents under the age of 10 or over the age of 19; (e) focused on interventions or measurement validity and did not address psychosocial factors; (f) were a review, commentary, or dissertation; (g) were on an unrelated topic; (h) had no full text available.…”
Section: Methodsmentioning
confidence: 99%
“…If the provider is not already a member of, and deeply embedded within, the refugee or immigrant community, these strategies include partnering with cultural brokers or community health workers who are individuals from the community the provider seeks to serve. In doing so, mental health services are likely to be more effective, trusted, and culturally responsive (Brar-Josan & Yohani, 2019;Cardeli, Phan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%